IDENTITAS BUDAYA DALAM KOMUNIKASI ANTAR-BUDAYA: Kasus Etnik Madura dan Etnik Dayak - Iskandar, Dadan (P2KK LIPI, 2004)
As nation which multiethnic, Indonesia has potency of conflict. From perspective of intercultural communications, inter-ethnic conflict can initiate from cultural identity differences which communicated ethnocentrism. Analyse for ethnical conflict of Dayak and Madura in West Kalimantan show that stereotype - representing the part of self perception through ascription process - as most potential property of cultural identity that generate internal issue in intercultural communications. This Stereotype was afirmed through conflict historically and culturally developed; built by both bloodthirsty tradition